1996
DOI: 10.1152/ajpregu.1996.270.1.r217
|View full text |Cite
|
Sign up to set email alerts
|

Formation and actions of 20-hydroxyeicosatetraenoic acid in rat renal arterioles

Abstract: The present study examined whether preglomerular arterioles of the rat produce 20-hydroxyeicosatetraenoic acid (20-HETE) and whether 20-HETE is vasoactive on these vessels. Raf preglomerular arterioles produced 20-HETE (4.8 +/- 1.0 pmol.min-1.mg-1, n = 7) and, to a lesser extent, 14-, 15-, 11-, and 12-dihydroxyeicosatetraenoic acid, 6-ketoprostaglandin F/alpha and prostaglandin E2 when incubated with [14C]larachidonic acid. The results of immunoblotting and reverse-transcription polymerase chain reaction exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
243
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(254 citation statements)
references
References 0 publications
9
243
2
Order By: Relevance
“…All of the isoforms catalyze the ω-and ω-1 hydroxylation of arachidonic acid to produce 20-HETE [2,5,[25][26][27]. Ito et al [28] used isoform specific primers to amplify 4A isoforms individually and found that the expression of CYP4A1 mRNA was very low but that CYP 4A2 and 4A3 mRNA are constitutively expressed throughout various nephron segments and the renal vessels in male SD rats.…”
Section: Discussionmentioning
confidence: 99%
“…All of the isoforms catalyze the ω-and ω-1 hydroxylation of arachidonic acid to produce 20-HETE [2,5,[25][26][27]. Ito et al [28] used isoform specific primers to amplify 4A isoforms individually and found that the expression of CYP4A1 mRNA was very low but that CYP 4A2 and 4A3 mRNA are constitutively expressed throughout various nephron segments and the renal vessels in male SD rats.…”
Section: Discussionmentioning
confidence: 99%
“…The cytochrone P 450 pathway is also a route of arachidonic acid metabolism in the kidney [42], and 20-HETE generated by cytochrome P 450 has a constrictor effect on afferent arterioles [45] and thus may also contribute to the exaggerated TGF response in Ang II-dependent hypertension.…”
Section: Effects Of Angiotensin II On Juxtaglomerular Apparatusmentioning
confidence: 99%
“…Among various existing pulmonary arterial vasodilators, such as NO, sildenafil, and cGMP (24,25), 20-hydroxyeicosatetraenoic acid (20-HETE), a cytochrome P-450 4A metabolite of arachidonic acid, consistently dilates pulmonary arteries in several species, including humans (2). 20-HETE induces a relaxation in bovine pulmonary arteries, whereas it induces a contraction in bovine renal arteries (12,15), suggesting a specific mode of action of 20-HETE according to vascular beds. Interestingly, on one hand, hypoxia blocks the conversion of arachidonic acid into 20-HETE in rabbit lung (34), whereas, on the other hand, chronic hypoxia induces sustained elevated pulmonary arterial pressure and vascular remodeling leading to PAH (26), suggesting a potential role for a lower -hydroxylase activity and a decreased production of endogenous 20-HETE in chronic hypoxia-induced PAH.…”
mentioning
confidence: 94%